THE JUDICIALIZATION OF HEALTH AND BUDGETARY IMPACTS IN INTERNATIONAL BORDER MUNICIPALITIES - de Fátima Corbolin Mergener, Solange; de Carvalho, Manoela [UNESP] (Instituto Rede de Pesquisa Empirica em Direito (REED), 2024)
The search for support from Brazilian judicial institutions to access to health technologies such as medicines, procedures, products such as prostheses, industrialized food, and hospital beds that are unavailable to the citizens, involves costs for the Unified Health System (SUS) and brings consequences to the public budget. This study aimed to analyse the judicialization of health and the financial impact on municipalities in the 9th Health Region of Paraná, based on secondary data obtained from the website of Brazil’s National Council of Justice from a sample of 295 technical notes, from 2020 to 2022. The results show that more than 60% of the lawsuits were favorable to the plaintiffs, most of them filed to access goods and services already incorporated into the SUS. Medication was the most claimed technology, with prices ranging from R$21.78 to R$474,676.24. Ophthalmology and oncology were the most judicialized medical specialties. The conclusion is that the Judiciary, in seeking to guarantee the right to goods and services already promised and incorporated into the SUS, ensures the individual right enshrined in the Federal Constitution, but interferes in the planning of health actions for the collective. We suggest the possibility of countering judicialization with SUS management actions with health promotion and illness prevention policies from the first level of health care and through the implementation of broader and more universal social policies.
A JUDICIALIZAÇÃO DA SAÚDE E OS IMPACTOS ORÇAMENTÁRIOS EM MUNICÍPIOS DE FRONTEIRA INTERNACIONAL
Keywords: financing; lawsuit; public policy; right to health; SUS